1980
DOI: 10.1103/physrevlett.45.1311
|View full text |Cite
|
Sign up to set email alerts
|

Breakup-Fusion Description of Massive Transfer Reactions with Emission of Fast Light Particles

Abstract: It is shown that massive transfer reactions emitting energetic light particles can be described in terms of two-step processes, in which breakup of the projectile takes place first, followed by an absorption of the massive partner of the broken-up pair by the target.PACS numbers: 25.70. Be, 24.50.+g

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
93
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(100 citation statements)
references
References 16 publications
5
93
2
Order By: Relevance
“…Moreover, in our recent observation [5], we found a diffused boundary in the -window that may penetrate near the barrier. Different theoretical models [9][10][11][12] have been presented for the ICF, but anyhow those are not able to explain the underlying reaction dynamics at energies below 10 MeV/nucleon. Hence, in order to study the ICF reaction dynamics at low incident energies, we have measured the excitation functions (EFs) of evaporated residues in 16 O + 165 Ho system at energies ≈ 4-7 MeV/nucleon.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in our recent observation [5], we found a diffused boundary in the -window that may penetrate near the barrier. Different theoretical models [9][10][11][12] have been presented for the ICF, but anyhow those are not able to explain the underlying reaction dynamics at energies below 10 MeV/nucleon. Hence, in order to study the ICF reaction dynamics at low incident energies, we have measured the excitation functions (EFs) of evaporated residues in 16 O + 165 Ho system at energies ≈ 4-7 MeV/nucleon.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies [13] on spherical targets showed involvement of -values in ICF lower than critical as well, giving rise to conflicting reports on the a e-mail: dpsingh19@gmail.com dependence of ICF on the angular momentum. Further, it may be pointed out that the available theoretical models [9,[14][15][16][17] satisfactorily predict the magnitude of ICF contribution, to some extent, in some cases at energies ≈10 MeV/nucleon, but none of these models is able to successfully explain such data at low energies. In view of the above, a clear picture of the mechanism of ICF has yet to emerge, particularly at energies ≈3-5 MeV/nucleon.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally measured spin distributions of the residues produced as incomplete fusion products associated with fast α and 2α-emission channels observed in forward cone are found to be distinctly different from those of the residues produced as complete fusion products. The mean value of input angular momentum J 0 for evaporation residues produced through xn channels (complete fusion products) is found to be J 0 ≈ 7ħ, while the mean value of input angular momentum J 0 for the residues produced through direct αxn and 2αxn channels (incomplete fusion products) in forward cone, are found to be J 0 ≈ 9ħ and ≈ 12 ħ respectively for 16 O + 124 Sn (spherical) system [7]. The mean value of input angular momentum J 0 for the system 16 O + 169 Tm (deformed) reported in ref.…”
mentioning
confidence: 94%
“…Various dynamical models viz. Break-Up Fusion (BUF) [7], Sumrule [8], Promptly Emitted Particles (PEPs) [9], Hot Spot [10], Multistep Direct Reaction theory [10] …”
Section: Introductionmentioning
confidence: 99%